If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 1 = t + 8 Reorder the terms: 1 + 2t = t + 8 Reorder the terms: 1 + 2t = 8 + t Solving 1 + 2t = 8 + t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. 1 + 2t + -1t = 8 + t + -1t Combine like terms: 2t + -1t = 1t 1 + 1t = 8 + t + -1t Combine like terms: t + -1t = 0 1 + 1t = 8 + 0 1 + 1t = 8 Add '-1' to each side of the equation. 1 + -1 + 1t = 8 + -1 Combine like terms: 1 + -1 = 0 0 + 1t = 8 + -1 1t = 8 + -1 Combine like terms: 8 + -1 = 7 1t = 7 Divide each side by '1'. t = 7 Simplifying t = 7
| 2(a+1)=14+a | | R=60q+q^2 | | 3t+1=t+8 | | =60Q-Q^2 | | xsquare+37x+210=0 | | 14=2(a-2) | | iz^2-3z-2i=0 | | iz^2+3z-2i=0 | | 3t+3=t+8 | | 14+a=2(a-4) | | 10x^3-7x-3=0 | | kx^2-kx^2=-1 | | X+35=6x | | 4-7a+15-8a-21= | | 1.5x+4=0.25x-3 | | 16h^4-8h^2+1=0 | | 0.875t-2=0.375t+9 | | 2(4x-1)+3x=-13o | | 22.67647059= | | 6=4*-10 | | y=29 | | 5x-4=x+32 | | 5x^4+16x^3+12x^2=0 | | 27a^3+64= | | x^2+3x+88=0 | | x(x+3)=88ft^2 | | 2x-9=57 | | 4(-2c+1)=3c-18 | | 28x^2-x-15=0 | | 12x^3-42x+18=0 | | 4x-9-12-3x=18 | | 14w^2+8w=0 |